A crise do estado social e democrático de direito no Brasil - Leite, Vinícius Lapoian (2019)
The aim of this paper is to focus on the reflection on the Brazilian Social and Democratic State of Law crisis, especially regarding the democratic regime crisis – or, as it has been called by some authors, “democratic recession” – and the factors that involve Brazil in this situation. The importance of this issue is revealed by the fact that, since the beginning of the 21st century, several countries in the world, including those with a consolidated democratic regime, have been inserted a period when democratic rules are being questioned or weakened precisely by political leaders who were elected by popular vote. As a methodology, we sought to contribute in homeland and international doctrine; as well as in historical notes about Brazil, which will allow to provide historical and current examples about the proposed theme